SYSTEMATIC REVIEW : PENYULUHAN MENGGUNAKAN MEDIA AUDIOVISUAL INTERAKTIF TERHADAP PERUBAHAN PERILAKU ANAK DALAM MENJAGA KESEHATAN GIGI DAN MULUT - Kirana Patrolina Sihombing; Nelsi natalia Gulo (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2023)
Dental and oral health is a serious issue in Indonesia, especially among school-age children. Dental and oral health is influenced by a person's behavior, knowledge, attitudes and actions. The use of appropriate media, such as audiovisual, is one of the efforts to improve children's behavior in maintaining dental health. The purpose of this systematic review study was to find out the effect of dissemination using interactive audiovisual as a medium on changes in children's behavior in maintaining oral health. This research is a systematic review of 10 journals published from 2016-2020 which have related titles, about the effect of dissemination using interactive audiovisuals as a medium for changes in children's behavior in maintaining dental and oral health. Through the research results, it is known that the behavior of children before dissemination is 100% in the fair category, and after dissemination it becomes 100% in the good category, and the most widely used dissemination media is video, reaching 50%. The conclusion of this study is that interactive audiovisual media has more influence on changes in children's behavior in maintaining dental and oral health. This study recommends the health center to provide dissemination to children using audiovisuals to achieve optimal dental and oral health